The Reception of Machiavelli in Early Modern Spain - Howard, Keith David (Suffolk : Boydell & Brewer, 2014)
Arguing against historians of Spanish political thought that have neglected recent developments in our understanding of Machiavelli's contribution to the European tradition, the thesis of this book is that Machiavellian discourse had a profound impact on Spanish prose treatises of the sixteenth and seventeenth centuries. After reviewing in chapter 1 Machiavelli's ideological restructuring of the language of European political thought, in chapter 2 Dr. Howard shows how, before his works were prohibited in Spain in 1583, Spaniards such as Fadrique Furió Ceriol and Balthazar Ayala used Machiavelli's new vocabulary and theoretical framework to develop an imperial discourse that would be compatible with a militant understanding of Catholic Christianity. In chapters 3, 4 and 5 he demonstrates in detail how Giovanni Botero, Pedro de Ribadeneyra, and their imitators in the anti-Machiavellian reason-of-state tradition in Spain, attack a straw figure of Machiavelli that they have invented for their own rhetorical and ideological purposes, while they simultaneously incorporate key Machiavellian concepts into their own advice. Keith David Howard is an Assistant Professor of Spanish at Florida State University.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).